Discrepancy Between Knowledge and Behavior Among Mothers of Children With Diarrhea - Yuniarti, Kwartarini Wahyu (Faculty of Psychology, Universitas Surabaya, 2011)
Diarrheal morbidity and mortality remain a serious burden for children in developing countries. In Indonesia, approximately 15% of deaths among infants and 25% of deaths among children aged between 1 to 4 years are caused by diarrhea. A number of studies have shown that poor hygiene practices are significantly associated with diarrhea. However, the relationship between knowledge and behavior in relation to diarrhea does not seem to be consistent across studies. The objectives of this study were to examine the discrepancy between mothers’ hygiene-related knowledge and practices; and also to identify the factors explaining the discrepancy. This community-based cross- sectional study took place in Pituruh and Gebang Sub-districts, Purworejo. The participants are random samples of mothers of children aged between 3-36 months. There is no significant statistical relationship between hygiene-related knowledge and practices (r= .01, p> .05). The discrepancy between hygiene-related knowledge and practice seems to be due to the relatively low perceived benefits and high perceived barriers for practicing hygiene properly. Morbiditas dan mortalitas diare pada anak masih merupakan hal yang sangat serius di negara berkembang. Di Indonesia, diare menyebabkan sekitar 15% kematian bayi dan 25% kematian anak berusia 1– 4 tahun. Hasil studi tentang hubungan antara pengetahuan dan perilaku kebersihan tampaknya tidak konssten. Studi ini bertujuan menguji apakah ada hubungan antara pengetahuan dan perilaku kebersihan pada ibu, dan mengindentifikasi faktor yang memengaruhi adanya diskrepansi antara perilaku dan pengetahuan kebersihan. Lokasi studi: Kecamatan Pituruh dan Gebang, Purworejo. Penelitian ini merupakan studi belah-silang terhadap para ibu yang memiliki batita dengan anak usia 3 – 36 bulan. Tidak ada hubungan signifikan secara statistik antara pengetahuan dan perilaku kebersihan. Diskrepansi antara pengetahuan dan perilaku kebersihan disebabkan oleh rendahnya manfaat dan tingginya hambatan yang dirasakan ketika mempraktikkan pola hidup sehat yang benar.